The Method of Subsuper Solutions for Weighted p(r)-Laplacian Equation Boundary Value Problems - Zhimei Qiu (Journal of Inequalities and Applications, 2008)
This paper investigates the existence of solutions for weighted p(r)-Laplacian ordinary boundary value problems. Our method is based on Leray-Schauder degree. As an application, we give the existence of weak solutions for p(x)-Laplacian partial differential equations.